EFFECTIVENESS OF SPECIALIZED KINESITHERAPY IN CHILDREN WITH SPASTIC HEMIPLEGIC CEREBRAL PALSY - Margarita Avramova (Peytchinski Publishing, 2021)
Purpose: The aim of this study was to investigate the effect of Doman-Delacato and Perfetti methods in addition to routine kinesitherapy for children with spastic hemiplegic cerebral palsy (CP). Material and Methods: 60 children with a spastic hemiplegic CP were randomly divided into two groups - the control group (CG) received routine kinesitherapy method, and the experimental group (EG) received, in addition, specialized neurodevelopmental methods of Doman-Delacato and Perfetti. For children in both groups, kinesitherapy was applied three times a week for 50 min each procedure. Assessment was done using Ashworth Modified Scale, the Holt and Hoskins - Squires Test and GMFM - 88. The study period ran from April 2018 to November 2018. The evaluation was done before and 8 months later. Data were analyzed using GraphPad Prism version 3.0 andSPSS 19.0. The level of significance was accepted as p<0.05. Results: 60children, 27 girls and 33 boys managed (X±SD) for EG 4.8±1.3 and for CG 5.06±1.4 were included. Muscle spasticity in EG children decreases much earlier and more than in children in CG. Man Witney criteria show statistically significant differences at the end of the treatment (р=0,03<α=0,05). Hottest and GMFM-88dataobtainedalsoreceivedstatisticallysignificantdifferencesof t - criteria between initial and final measurements in EG. Conclusions: EG children improvement is better and occurs much earlier. Therefore, we could assert that our methodology optimizes the treatment of children with CPD and improves their quality of life.